2017
DOI: 10.1021/acs.jafc.7b03669
|View full text |Cite
|
Sign up to set email alerts
|

Foams Stabilized by β-Lactoglobulin Amyloid Fibrils: Effect of pH

Abstract: β-Lactoglobulin fibrils could serve as a surface-active component and form adsorption layers at the air/water interface. In this study, the physical parameters related to the surface adsorption, foaming, and surface properties of β-lactoglobulin fibrils as a function of pH (2-8) were investigated. Results showed that an increase of pH from 2 to 5 led to a rise of the viscoelastic modulus of the surface adsorption layer and half-life time (t) of foams, but it decreased foamability. When the pH was close to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…We varyÊ between 0.1 and 2, which affects the surface tension through the Langmuir equation of state, Eq. (14). With larger values ofÊ, the surface tensions acting at the vertex are weaker, and therefore the film takes longer to reach its final length, as shown in Fig.…”
Section: The Effect Of Surface Elasticitymentioning
confidence: 89%
See 2 more Smart Citations
“…We varyÊ between 0.1 and 2, which affects the surface tension through the Langmuir equation of state, Eq. (14). With larger values ofÊ, the surface tensions acting at the vertex are weaker, and therefore the film takes longer to reach its final length, as shown in Fig.…”
Section: The Effect Of Surface Elasticitymentioning
confidence: 89%
“…The surface dilatational modulus of protein solutions is strongly dependent on the concentration and pH of the sample [14]. The BLG sample used in our experiments has a concentration of 50g/l and pH = 7, for which the real component of the dilatational surface modulus is E ≈ 40 [13], but values up to 110 have been found [15].…”
Section: Predicting the Gibbs Elasticity Ementioning
confidence: 93%
See 1 more Smart Citation
“…Self-assembly of protein fibrils produced by heating dilute solutions of proteins at low pH have been investigated by various workers and reviewed recently by Mohammadian and Madadlou [37]. Thus Peng et al [38] have investigated -lactoglobulin fibrils and found that film strength and bubble stability is a maximum close the pI, where the absorbed films have highest dilatational moduli but at the expense of foamability. Raising the pH slightly above the pI and re-introducing some charge to the fibrils improved foamability whist maintaining good foam stability.…”
Section: Protein-based Nanoparticles and Microgelsmentioning
confidence: 99%
“…Foam stability increased as the pH increased from 2 to 8, and the BLGFs provided the optimum foam stability when the pH approached the isoelectric point. 28 The mechanisms of foam instability include liquid drainage caused by gravity and liquid transfer from the inter-bubble lamella to the plateau border, and foam collapse caused by lamellar rupture and disproportionation. 29,30 Many researchers have studied the functional properties of NGBLG, including gels, emulsions, interfaces, foams, etc.…”
Section: Introductionmentioning
confidence: 99%